Neurostimulation leads, intrathecal catheters and anchoring devices evolution - Laura Demartini; Gianluca Conversa; Luciana Armiento; Lucia Angelini; Cesare Bonezzi (Publiediting, 2015)
Many scientific studies highlight the usefulness of spinal cord stimulation and intrathecal therapy for the management of chronic pain syndromes resistant to pharmacological or less invasive interventional therapies. One of the possible complications of these techniques, reported in literature, is migration of the lead or catheter; thus the use of an anchoring system is considered mandatory. Every company that produces devices for neurostimulation or neuromodulation provides various anchoring devices evolved over time. In the study, the authors discuss about the most common anchoring devices based on their clinical experience.